2021
DOI: 10.1080/13537903.2021.1958493
|View full text |Cite
|
Sign up to set email alerts
|

“I’m just British—normal British”: Exploring Teachers’ and Pupils’ Conceptualisations of Religion(s) and Religious Belonging

Abstract: This article seeks to foreground the voices of primary school teachers and children-often silenced in research-and explore how they understand religion(s) and religious belonging. The findings draw on qualitative data investigating the narratives of teachers and pupils from five primary community schools in the West Midlands (England). The research shows that religious traditions in contemporary Religious Education classes still tend to be constructed as un-diverse, impermeable, monolithic wholes as teachers r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Research shows that this is already an issue, as teachers feel more comfortable teaching about 'world religions' and worldviews 'which adhere to their own sense of a "good life", such as the golden rule, but ignor[e] aspects of religion(s) with which they disagree' (Flanagan, 2020, 12-13). Benoit's (2020) research also shows that teachers are more likely to focus on religious and non-religious philosophical convictions that promote a 'good life', and avoid 'destructive spiritualities '. 5 By emphasising lived experiences and seeking 'to understand how worldview works in human life', the CoRE report's 'proposed worldview paradigm seeks to replace the current world religions paradigm' (Cooling et al, 2020, 39).…”
Section: Worldviews and The Classroommentioning
confidence: 94%
See 2 more Smart Citations
“…Research shows that this is already an issue, as teachers feel more comfortable teaching about 'world religions' and worldviews 'which adhere to their own sense of a "good life", such as the golden rule, but ignor[e] aspects of religion(s) with which they disagree' (Flanagan, 2020, 12-13). Benoit's (2020) research also shows that teachers are more likely to focus on religious and non-religious philosophical convictions that promote a 'good life', and avoid 'destructive spiritualities '. 5 By emphasising lived experiences and seeking 'to understand how worldview works in human life', the CoRE report's 'proposed worldview paradigm seeks to replace the current world religions paradigm' (Cooling et al, 2020, 39).…”
Section: Worldviews and The Classroommentioning
confidence: 94%
“…The WRP has been the object of criticismespecially from post-colonial scholarsfor being entrenched in Western Christianity (Smith, 1964;Cox, 2016;Masuzawa, 2005). A number of ethnographic studies have also shown that when RE is taught through the lens of the WRP, the subject often leads to restrictive and normative discursive constructions of reified "world religions", and fails to equip learners with the tools to navigate our diverse societies (Benoit, 2020;. The CoRE report agrees with this critique:…”
Section: Worldviews and The Classroommentioning
confidence: 96%
See 1 more Smart Citation